The Challenges of Direct Licensing Implementation in Indonesia’s Music Royalty System: Assessing Copyright Law from the Perspective of Creators - Maulana, Rivo Denra; Dirkareshza, Rianda (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the challenges in implementing direct licensing within Indonesia’s music royalty management system and to assess its conformity with Law Number 28 of 2014 on Copyright and its implementing regulations. The main issue discussed is the absence of a clear legal framework governing direct licensing mechanisms, which leads to an imbalance between the economic rights of creators and the authority of the National Collective Management Organization (LMKN). This research employs a normative juridical approach with a qualitative descriptive analysis method, using literature studies of relevant legislation, legal doctrines, and actual cases such as the royalty disputes involving Agnez Mo and Ari Bias. The findings indicate that direct licensing has the potential to enhance legal certainty, transparency, and efficiency for creators, yet its implementation remains hindered by overlapping regulations and weak institutional infrastructure. Therefore, legal reform through the revision of the Copyright Law and its derivative regulations is necessary to explicitly recognize direct licensing as a legitimate mechanism in royalty management. Furthermore, strengthening the role of the Directorate General of Intellectual Property (DJKI) and transforming LMKN into an accountable facilitating body are essential steps toward establishing a fair and transparent royalty system that effectively protects the rights of music creators in Indonesia.